Li2B24: the simplest combination for a three-ring boron tube. Issue 5 (22nd January 2019) - Dong, Xue; Jalife, Said; Vásquez-Espinal, Alejandro; Barroso, Jorge; Orozco-Ic, Mesías; Ravell, Estefanía; Cabellos, José Luis; Liang, Wei-yan; Cui, Zhong-hua; Merino, Gabriel
Abstract : Herein we introduce a strategy employing lithium atoms as a scaffold to stabilize an embryo for boron tubes. Abstract : Herein we introduce a strategy employing lithium atoms as a scaffold to stabilize an embryo for boron tubes. The systematical exploration of the potential energy surface via evolutionary algorithms allowed us to find that Li2 B24 adopts a tubular structure formed by three stacked rings of eight borons each with two lithium atoms capping the tube. The lithium atoms are essential for stabilization because of the strong electrostatic interaction between the Li cations and the boron framework, and concomitantly, they compensate for the energy cost of distorting a quasi-planar or double ring B24 cluster.